Direct Synthesis of N-Monosubstituted Benzimidazol-2-ones via Ph3P–I2-Mediated Reaction of Hydroxamic Acids - Wiriya, Nittaya; Yamano, Dolnapa; Hongsibsong, Surat; Pattarawarapan, Mookda; Phakhodee, Wong (Synlett, 2022)
A facile approach for the synthesis of benzimidazolones via a Ph3P–I2 promoted reaction of hydroxamic acids is reported. Upon Lossen-type rearrangement of the O-activated hydroxamic acids, the in situ generated isocyanates undergo an intramolecular attack by ortho N-nucleophiles producing the cyclized products in good yields under mild conditions. The method allows the direct preparation of a single regioisomer of N-monosubstituted derivatives using readily accessible starting materials and low-cost reagents with broad substrate scope.
Keywords: benzimidazol-2-ones; hydroxamic acids; triphenylphosphine; iodine; Lossen rearrangement